Estimation of in-situ shear strength parameters of weathered granitic (masado) slopes using lightweight dynamic cone penetrometer - Tsuchida, T.; Athapaththu, Athapaththu; Kano, S.; Suga, K. (Japanese Geotechnical Society, 2011)
A major problem in the geotechnical approach to the stability of natural slopes is that there is usually little information on the in-situ geotechnical conditions, because of the extreme difficulty associated with ground investigations of steep slopes covered with vegetation. In this study, a lightweight dynamic cone penetration test (LWDCPT) has been introduced for a geotechnical survey of natural weathered granitic (Masado) slopes. Based on a series of direct shear tests, the internal friction angle and the apparent cohesion of reconstituted Masado soil were found to be fairly closely related to the void ratio and the degree of saturation in the soil. From the laboratory calibration tests, an equation was created to relate the dynamic cone resistance (qd) and the void ratio of reconstituted Masado under different degrees of saturation. Equations were developed to calculate the internal friction angle and the apparent cohesion from the value of qd for Masado at a known degree of saturation. LWDCPT and direct shear tests were carried out on undisturbed samples taken from a natural Masado slope. The estimated internal friction angle and the apparent cohesion calculated with the value of qd in the LWDCPTs agreed fairly well with those of tests on the undisturbed samples obtained in laboratory shear tests.